Critical process for the implementation of technology in sport organizations - Torres-Ronda, L.; Schelling, X. (Strength and Conditioning Journal, 2017)
The impact that technology has today and will have in the future in sport is unquestionable. We are constantly exposed to a multitude of new devices and products claimed to be "critical for performance success or injury prevention." this has led to a situation where sports organizations that are using or are considering the use of these tools can be, and are actually harassed by numerous promoters of the next "holy grail." this manuscript aims to provide a guideline to help organizations with the technology vetting process and on the implementation of technology